Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 11 - Further Topics in Algebra - 11.1 Sequences and Series - 11.1 Exercises - Page 1014: 38



Work Step by Step

$\sum ^{6}_{i=1}\left( 3i-2\right) =3\sum ^{6}_{i=1}i-\sum ^{6}_{i=1}2=\dfrac {3\times 6\times \left( 6+1\right) }{2}-6\times 2=51$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.